Analysis of High-Level Thinking Skills in Pancasila Education Learning at State Vocational Schools on Material Manage Diversity as Social Capital for National Development - Safitri, Laila Vika; Listyaningsih, Listyaningsih; Sarmini, Sarmini (IKIP Widya Darma Surabaya, 2025)
Objective: This study was conducted to analyze students' high-level thinking skills in learning Pancasila Education in the Chapter of Managing Bhinneka Tunggal Ika as Social Capital for National Development. The main focus of this study is to analyze the differences in students' high-level thinking skills in three main materials, namely the Origin and Meaning of Bhinneka Tunggal Ika, Gotong Royong as a Manifestation of Pancasila Economy, and the Principle of Gotong Royong Building Harmony in Diversity. Based on this focus, the formulation of the problem in this study is how students' high-level thinking skills in understanding the three materials. The substance of this research focuses on evaluating the development of students' high-level skills in each material, identifying the factors that influence them, and providing recommendations for more effective learning strategies in improving higher-level thinking skills. Methods: The research method used was preliminary research that was descriptive and did not conduct hypothesis testing. The research sample consisted of 36 students in class X and Pancasila Education teachers at State Vocational School 2 Surabaya, East Java. The data collection technique used documentation of written exam scores, questionnaire sheets, and interviews with teachers and students. Results: The results of the data obtained were analyzed using quantitative and qualitative descriptive analysis techniques. The results of the study show that 1). The students' high-level thinking skills are in the low and middle categories. Based on the results of the calculation, the material on the Principle of Mutual Cooperation in Building Harmony in Diversity, where the analysis skill score (C4) reached 63.42 in the medium category, evaluation (C5) 44,056 and created (C6) 43.39 which was classified as low category 2). The lowest indicators of high-level thinking skills are evaluation (C5) and creating (C6). 3). Teachers still use lecture methods and conventional teaching materials during learning. Novelty: This study provides a new perspective in measuring high-level thinking skills in the context of learning Pancasila Education in vocational schools, especially in understanding the three materials in the chapter on diversity and diversity. The results of this study are an important contribution to the development of digital flipbook interactive teaching materials with gamification-based interactive quizzes that are more effective with the aim of improving high-level thinking skills in Pancasila Education, especially in vocational schools that are still rarely studied in similar studies.